ANALISIS TEKNIK PENGERITINGAN RAMBUT DESAIN DALAM PRAKTIK TATA KECANTIKAN (PENDEKATAN KUALITATIF) - Angelina Puspita Sari; Dinda Rahmasari; Polmauli S; Sintya Roma O; Asrah Rezki Fauzani; Mutia Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Hair curling is an important competency in the field of beauty, aiming to produce a variety of curls according to the desired hair design. This study aims to analyze the role of hair curling techniques in improving practical skills in beauty. The method used is a literature study by reviewing various scientific sources that discuss hair curling techniques, tool use, and learning media in the field of beauty. The results of the study indicate that various hair curling techniques, such as alternating, zigzag, and spiral, produce different curl characteristics that can be adapted to the purpose of the hair design. In addition, the success of hair curling is influenced by mastery of the correct curling technique and the use of appropriate tools, while interactive and digital learning media have been proven to improve students' understanding, motivation, and learning outcomes. Thus, the integration of hair curling techniques, the use of appropriate tools, and effective learning media can support the improvement of practical skills and the quality of beauty learning.